2010
DOI: 10.1016/j.jcin.2010.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Transcatheter Occlusion of Patent Ductus Arteriosus in Infants Weighing ≤6 kg

Abstract: Percutaneous closure of PDA should be considered even in infants ≤6 kg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
73
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 12 publications
4
73
2
1
Order By: Relevance
“…Evidence on the risks of drug therapy or surgical PDA ligation26, 27 has led to growing interest in the use of percutaneous closure in premature infants 10, 15, 16, 28, 29, 30. The main finding of our 10‐year study is that, among a large cohort of infants born very premature and referred for percutaneous closure at weights <4 kg, the majority are successfully closed in the catheterization suite with evidence of improved pulmonary status following closure, but risk of arterial injury in these infants is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence on the risks of drug therapy or surgical PDA ligation26, 27 has led to growing interest in the use of percutaneous closure in premature infants 10, 15, 16, 28, 29, 30. The main finding of our 10‐year study is that, among a large cohort of infants born very premature and referred for percutaneous closure at weights <4 kg, the majority are successfully closed in the catheterization suite with evidence of improved pulmonary status following closure, but risk of arterial injury in these infants is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…Although investigators have reported that percutaneous closure of the PDA is the procedure of choice among infants ≥4 kg,10 the lower limit for safe closure remains unknown. While 4 kg as a weight‐cutoff is not evidence based, previous studies have excluded preterm infants <4 kg or reported no cases of percutaneous PDA closure below this weight threshold 11, 12, 13, 14.…”
Section: Discussionmentioning
confidence: 99%
“…Food And Drug Administration of USA has approved Amplatzer duct occluder (ADO) for pediatric patients with weight !6 kg. 5 The most important factors determining the success of PDA device closure are the weight of the baby, ductal size and anatomy, and the availability of suitable hardware. 6 Because of less complications, comparable success rates, less invasiveness, availability of suitable devices as compared to surgical ligation, PDA device closure is rapidly becoming a popular method in low weight for age pediatric patients with PDA which has favorable anatomy for device closure as in our case.…”
Section: Discussionmentioning
confidence: 99%
“…The Nitocclud coil was originally designed for closure of the PDA and normally results in closure rates of 94% in neonatal PDAs [4]. Its attractive diabolo-like shape and its soft recoil of the nitinol wire, which causes only minimal pressure on the surrounding tissue, were the reasons why it was chosen for the reported patient.…”
Section: Discussionmentioning
confidence: 99%